Fenomenology Masyarakat Islam Nusantara - Hakim, Lukman; Mukhlis, Zainal (The Sociology of Islam, 2024)
The formation of Islamic society in Indonesia is both dynamic and polycentric. Experts from various fields have assigned diverse labels, such as political Islam, cultural Islam, traditionalist Islam, modernist Islam, spiritual Islam (Islam Kebtinan), puritanical Islam, and so forth. However, these typologies are inseparable from two key influences: globally inspired views of Islam on the one hand and locally rooted views of Islam on the other. This article examines the phenomenology of Islamic society in Indonesia, with a particular focus on traditionalist Muslims, Islam kejawen, and puritanical Islam. Using a literature review of the religious symbols of researched Islamic society and employing phenomenological tools, the findings illustrate unique typologies of the Muslim people of Nusantara. Traditional Islamic society integrates religion and both sacred and profane aspects into an attitude of respect for the great intellectual and spiritual traditions of Islam. This respect is manifested through behavioral symbols such as the traditions of maintaining a sanad and adhering to a madzhab in addressing religious and socio-cultural matters. These practices are rooted in ideational symbols, such as the concept of the ukhuwah—basyariyah, wathaniyah, and diniyah— expressed through religious material symbols. In contrast, the phenomenological awareness of puritanical Islamic society emphasizes the sacred and profane by focusing on the authenticity and exotericism of Islam. Meanwhile, Javanese Islam perceives religion as an intersubjective awareness connecting God, nature, and the human self.